PENGGOLONGAN PERFORMANS 25 JENIS ROTAN INDONESIA BERDASARKAN KERAPATAN, KEKAKUAN, DAN KEKUATAN - Abdurachman; Jasni (BRIN Publishing, 2015)
Rattan signifies as one of non-wood forest products; and its role in Indonesia is essential as it provides approximately 80% of the world's rattan demand. Rattan finds numerous beneficial uses, such as ropes, weaving-items, mats, baskets, household utensils, handicraft goods, and furniture products. The utilization of rattans for such products are determined by among others their density (D), strength (MOR), and stiffness (MOE), whereby the greater those three values, then expectedly the better the rattan qualities as well as their corresponding rattan products. In South East Asia, including Indonesia, there are 2 outof 8 rattan genera that afford high economic values, namely Calamus and Daemonorops. In relevant, scrutiny on 25 Indonesia's rattan species has been conducted, and their possible classification based on density, MOR and MOE was examined. Those 25 species were dominated by Calamus spp. and Daemonorops spp. Scrutiny based on the entirely tested rattan properties (D, MOR and MOE) revealed that as many 16% of 25 rattan species could be grouped as class I(superior); 36% as class II (good), 32% as classIII (moderate) and 16% as class IV (poor). Further scrutiny also based on thoseoverall three rattan properties indicated that four species as the most prospectively utilized (from the highest rank) were Korthalsia rigida Bl, Calamus inops Becc.ex Heyne, and Calamus koordesianus Becc; meanwhile those as the least prospective similarly comprised Korthalsia zeppelii Burret, Plectocomiopsis geminiflora (Griff) Becc, and Calamus ornatus Blume dan Daemonorops malanocaetes BL.